The Influence of Gratitude Expression on Motivation Level Among Academic Staff - Azman, Nurshahirah (Selangor Humaniora Review, 2021)
The expression of gratitude and employees’ motivation level are always linked to each other for the big role they play in achieving individual and organisational goals. This study aims to investigate the perceptions of the academic staff towards the expression of gratitude and to also determine employee’s motivation level. A quantitative approach was employed, utilising a 27-item questionnaire that was administered through an online platform to 104 respondents. The participating respondents involved academic staff from public and private higher learning institutions in Selangor. The finding revealed a positive relationship between the expression of gratitude and the academic staffs’ motivation level. This is an important and valuable insight to be provided to the higher management of learning institutions in Malaysia for a possible consideration on the adjustment of the appreciation method in boosting employee’s motivation level.